Traditional Games “Boy-Boyan” and “Bebentengan” in Facilitating Social Skills in Elementary School: An Analysis - Rinaldi Yusup; Zaenal Abidin; Kalfajrin Kurniaji; Fajar Romadhon; Asti Fuji Astuti; Ucu Agustini Sri Mulyani; Sajidin Sajidin; Irfan Sofiyan (The Eastasouth Journal of Learning and Educations, 2026)
Traditional games are one of the cultural heritages that contain educational and social values for children’s development. However, technological advancement has caused traditional games to gradually be abandoned and replaced by digital games that tend to reduce direct social interaction. This study aimed to describe the role of traditional games boy-boyan and bebentengan in facilitating the social skills of elementary school students. The study employed a qualitative approach with a descriptive ethnographic design to examine the phenomenon of students’ cultural interactions. The research subjects were fifth-grade students at SDN 1 Kebonpedes. Data collection techniques were conducted through observation, interviews, documentation, and literature studies. The findings revealed that the boy-boyan game was highly effective in facilitating children’s social skills. Children were required to demonstrate cooperation and effective communication when determining tasks, arranging roof tiles, and throwing the ball. Meanwhile, the bebentengan game also effectively facilitated children’s social skills because the players were encouraged to cooperate and communicate while guarding the fortress, capturing opponents, and avoiding enemy attacks. Traditional games help students learn to resolve conflicts fairly and develop positive social relationships with peers, which can serve as an adaptive alternative for character education in elementary schools.